Detection of Total Aflatoxins in Groundnut and Soybean Samples in Yemen Using Enzyme-Linked Immunosorbent Assay - Safwan Ahmed Abdullah Murshed; Nafees Bacha; Talal Alharazi (Journal of Food Quality)
Aflatoxins are fungal toxins that have mutagenic and carcinogenic effects, especially hepatocellular carcinoma effect. This work aimed to investigate the presence of aflatoxins in groundnuts and soybeans that are consumed in Yemen. The samples were collected from three different regions in Yemen (Sana’a, al-Hodeida, and Aden), and they were divided into two groups. The concentration of total aflatoxins was analyzed by enzyme-linked immunosorbent assay (ELISA). Aflatoxins were determined in 89 groundnut and 65 soybean samples. The results showed that 85.39% (76/89) of groundnut and 72.3% (45/65) of soybean samples were contaminated with aflatoxins. In addition, in 49.44% and 27.6% of the groundnut and soybean samples, total aflatoxins exceed the acceptable level of European Commission (4 μg/kg), while in only 6.2% of soybean samples and 22.47% of groundnut samples, total aflatoxins were beyond the maximum limit of FDA/Yemen standards (20 μg/kg). The results showed that the aflatoxin contamination in the groundnut and soybean samples may be considered a significant risk for public health. The present study is the first to report the data on the presence of aflatoxins in groundnut and soybean samples in Yemen.